Addition to the known long-horned beetle fauna of the Bolivian Andes: A new lycid-like species of Mimolaia Bates, 1885 (Coleoptera, Cerambycidae, Lamiinae, Caliini) - Perger, Robert; Santos-Silva, Antonio (Zootaxa, 2019)
Mimolaia batesi sp. nov. from Bolivian Yungas forest is described and illustrated. The new species likely displays Batesian mimicry associated with slender Lycidae species having black elytra and orange/reddish pronotum laterally.